Synthesis, Structure, and Reactivity of (?5: ?1-C5me4(Ch2) 2nme2)Re(Co)2. Electron Transfer Behavior of a Nitrosyl Derivative - Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A (Elsevier, 2014)
The UV irradiation of a hexane solution of the complex (?5- C5Me4(CH2)2NMe2)Re(CO) 3 (1) afforded the chelated species (?5: ?1-C5Me4(CH2) 2NMe2)Re(CO)2 (2). The molecular structure of 2 has been determined by X-ray crystallography. The reaction of 2 with two-electron donor ligands yields (?5-C5Me 4(CH2)2NMe2)Re(CO)2(L) (1, L = CO; 3, L = PMe3). The chelated species 2 also reacts with MeOTf, HBF4, and I2 to form the cationic compounds trans-[(?5-C5Me4(CH2) 2NMe2)Re(CO)2X]+ ([4]+, X = Me; [5]+, X = H; [6]+, X = I). The trans stereochemistry of 4-6 have been assigned on the basis of ?(CO) IR intensities and 13C NMR spectroscopy. Also, complex 2 reacts with nitrosyl tetrafluoroborate to yield [(?5-C5Me 4(CH2)2NMe2NO)Re(CO) 2(NO)]BF4 ([7]2+). The redox behavior of the {ReNO}6 complex [7]2+ was studied and the products obtained after two-electron reduction were characterized by IR. DFT calculations were done to optimize the structure of [7]2+ and to study the effect of the sidearm coordination on the electronic structure of a cyclopentadienyl {ReNO}8 complex. © 2014 Elsevier B.V. All rights reserved.